Dependencias temporales y cambios institucionales en la América hispánica a fines del siglo XVIII e inicios del siglo XIX - Zacarías Moutoukias (Historia Crítica, 2015)
This article questions the explanatory capacity of common linear and predetermined visions of social change. In their place, and on the basis of a meticulous approach to a case study, it provides clues to a history attentive to its protagonists, a history of the actors and the processes in which the intersections, the plots, and their dynamics represent the place of possible explanations. Resuming the political and economic aspects of the “process of independence” in the transition from the 18th to the 19th century, this article poses the need to re-establish institutional trajectories of change based on complex devices and changing capacities of mobilization, i.e., recognizing and integrating the random dynamics of its own historicity.